Pengembangan Model Konservasi Pesisir Berbasis Community Based Ecotourism dalam Mendukung Pembangunan Berkelanjutan di Pantai Bohay, Desa Binor, Kabupaten Probolinggo: Pengembangan konservasi pesisir dan peran masyarakat dalam mendukung pembangunan berkelanjutan - Saiful Islam; Tatang Mitra Setia; Nonon Saribanon (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2026)
This study examines the development of a coastal conservation model based on Community-Based Ecotourism to support sustainable development in Bohay Beach, Binor Village, Probolinggo. Using a qualitative approach through interviews, observations, and document analysis, the research reveals that Bohay Beach has experienced ecological pressure due to increasing tourism activities, including waste accumulation, habitat degradation, and declining coastal vegetation. However, community participation, local regulations, and collaborative governance between village authorities, community groups, and private partners have strengthened conservation efforts. The findings show that the CBE based model enhances ecological resilience through coral transplantation, mangrove rehabilitation, and marine monitoring, while also providing economic benefits through tourism services, MSME development, and job creation. Social welfare improves with stronger community cooperation, environmental awareness, and broader involvement in conservation programs. Furthermore, the integration of climate adaptation initiatives, such as the “Kampung Iklim” program, reinforces long-term ecosystem sustainability. Overall, the study concludes that the CBE-based conservation model effectively integrates ecological, economic, and social dimensions, making it a strategic framework for sustainable coastal development in Binor Village